O programa mata ciliar no estado do Paraná - Araújo, José Andre de (2014)
This study aims to analyze the Riparian Program, it is necessary that all of society contributes to the protection of water, and there is awareness of key people involved in the degradation of these areas. Riparian vegetation types are located on the banks of rivers, streams, lakes, dams and springs, is also known as gallery forest, lowland forest, riparian vegetation or forest. Considered by the Federal Forest Code as "permanent preservation area". The removal of riparian vegetation leads to loss of terrestrial and aquatic biodiversity, and other ecological, social and economic impacts, such as the intensification of erosion processes with the appearance of furrows and gully erosion and silting of reservoirs, springs and watercourses, reduction of soil productivity and increased emission of greenhouse gases. The process of recovery of riparian forests should be participatory process and footwear with a strong environmental education component. When thinking about restoration of riparian forests, it is necessary to know how they were before they were destroyed. The best solution to this is to copy nature, nature selects trees that are capable of living in each place, so in a land brejosa some types of trees grow in stony land, other. To carry out this research on the recovery of riparian forests was made a literature focusing on the Laws that protect it, and retrieval of such importance.